Aggregation and organic matter in subarctic Andosols under different grassland management - Lehtinen, Taru; Lair, Georg J.; Leeuwen, Jeroen P. Van; Blum, Winfried E.H.; Bloem, Jaap; Steffens, Markus; Gísladóttir, Guðrún; Ragnarsdóttir, Kristín Vala (Taylor & Francis, 2015)
Quantity and quality of soil organic matter (SOM) affect physical, chemical, and biological soil properties, and are pivotal to productive and healthy grasslands. Thus, we analyzed the distribution of soil aggregates and assessed quality, quantity, and distribution of SOM in two unimproved and improved (two organic and two conventional) grasslands in subarctic Iceland, in Haplic and Histic Andosols. We also evaluated principal physicochemical and biological soil properties, which influence soil aggregation and SOM dynamics. Macroaggregates (>250 µm) in topsoils were most prominent in unimproved (62–77%) and organically (58–69%) managed sites, whereas 20–250 µm aggregates were the most prominent in conventionally managed sites (51–53%). Macroaggregate stability in topsoils, measured as mean weight diameter, was approximately twice as high in organically managed (12–20 mm) compared with the conventionally managed (5–8 mm) sites, possibly due to higher organic inputs (e.g., manure, compost, and cattle urine). In unimproved grasslands and one organic site, macroaggregates contributed between 40% and 70% of soil organic carbon (SOC) and nitrogen to bulk soil, whereas in high SOM concentration sites free particulate organic matter contributed up to 70% of the SOC and nitrogen to bulk soil. Aggregate hierarchy in Haplic Andosols was confirmed by different stabilizing mechanisms of micro- and macroaggregates, however, somewhat diminished by oxides (pyrophosphate-, oxalate-, and dithionite-extractable Fe, Al, and Mn) acting as binding agents for macroaggregates. In Histic Andosols, no aggregate hierarchy was observed. The higher macroaggregate stability in organic farming practice compared with conventional farming is of interest due to the importance of macroaggregates in protecting SOM and soils from erosion, which is a prerequisite for soil functions in grasslands that are envisaged for food production in the future.